Transcriptome Analysis Identifies Two Ethylene Response Factors That Regulate Proanthocyanidin Biosynthesis During Malus Crabapple Fruit Development - Li, Hua; Han, Mingzheng; Yu, Lujia; Wang, Sifan; Zhang, Jie; Tian, Ji; Yao, Yuncong (Frontiers in Plant Science, 2020)
Proanthocyanidins (PAs) are a class of flavonoid compounds in plants that play many important roles in pest and disease resistance and are beneficial components of the human diet. The crabapple (Malus) provides an excellent model to study PA biosynthesis and metabolism; therefore, to gain insights into the PA regulatory network in Malus plants, we performed RNA-seq profiling of fruits of the ‘Flame’ cultivar at five sequential developmental stages. KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis showed that differentially expressed genes (DEGs) related to the functional category ‘plant hormone signal transduction’ were significantly enriched during fruit development. Further analysis showed that ethylene signal transduction pathway genes or response genes, such as ERS (ethylene response sensor), EIN3 (ETHYLENE INSENSITIVE 3) and ERFs (ethylene response factors), may play an important role in the regulatory network of PA biosynthesis. Additionally, 12 DEGs, including 10 ERFs, 1 MYB, and 1 bHLH transcription factor, associated with PA biosynthesis were identified using WGCNA. The expression patterns of these genes correlated with PA accumulation trends and transcriptome data from qRT-PCR analysis. The expression of RAP2-4 (RELATED TO APETALA 2-4) and RAV1 (related to ABI3/VP1), which belong to the ERF transcription factor family, showed the greatest correlations with PAs accumulation among the 12 identified TFs. Agrobacterium mediated-transient overexpression of the RAP2-4 led to an increase in PA abundance in crabapple leaves and apple fruits, and the opposite results were observed in RAV1-overexpressed crabapple leaves and apple fruits. Moreover, a yeast one-hybrid assay showed that RAP2-4 and RAV1 specifically bound the promoters of the PA biosynthetic genes McLAR1 and McANR2, respectively. These results indicate that RAP2-4 act as an inducer and RAV1 act as a repressor of PA biosynthesis by regulating the expression of the PA biosynthetic genes McLAR1 and McANR2. Taken together, we identified two potential regulators of PA biosynthesis and provide new insights into the ethylene-PA regulatory network.